Correlations of brain structure with the social behavior of 15q11-13 duplication mice, an animal model of autism - Zhilei Zhao; Naohiro Okada; Sho Yagishita; Noriaki Yahata; Nobuhiro Nitta; Sayaka Shibata; Yoshifumi Abe; Susumu Morita; Eureka Kumagai; Kenji F. Tanaka; Tetsuya Suhara; Toru Takumi; et al. (Neuroscience Research)
Duplication of chromosome 15q11–13 has been reported to be one of the most frequent cytogenetic copy number variations in autism spectrum disorder (ASD), and a mouse model of paternal 15q11–13 duplication was generated, termed 15q dup mice. While previous studies have replicated some of the behavioral and brain structural phenotypes of ASD separately, the relationship between brain structure and behavior has rarely been examined. In this study, we performed behavioral experiments related to anxiety and social behaviors and magnetic resonance imaging (MRI) using the same set of 15q dup and wild-type mice. 15q dup mice showed increased anxiety and a tendency toward alterations in social behaviors, as reported previously, as well as variability in terms of sociability. MRI analysis revealed that a lower sociability index was correlated with a smaller gray matter volume in the right medial entorhinal cortex. These results may help to understand how variability in behavioral phenotypes of ASD arises even in individuals with the same genetic background and to determine the individual differences in neurodevelopmental trajectory correlated with specific brain structures that underlie these phenotypes.